Stock structure of the Brazilian sardine Sardinella brasiliensis from Southwest Atlantic Ocean inferred from otolith elemental signatures - Schroeder, Rafael; Schwingel, Paulo R.; Pinto, Edgar; Almeida, Agostinho; Correia, Alberto T. (Fisheries research, 2022)
The Brazilian sardine (Sardinella brasiliensis) supports the most important pelagic fishery in the southeast-south Brazil. The first studies on the population structure of S. brasiliensis suggested the existence of two stocks taking into account distinct regional somatic growth rates and spawning areas. However, subsequent works were unable to confirm this scenario, and at present for fisheries management purposes a single stock is considered in Brazil. In order to unravel the stock structure of S. brasiliensis, ninety adult individuals (two-year-old fish) were collected between February and October 2018 in three fishing grounds within its distribution area [Rio de Janeiro (RJ), Santa Catarina (SC) and Rio Grande do Sul (RS)]. Multi-elemental signatures of whole otoliths were determined using inductively coupled plasma mass spectrometry and combined with basic biological data (somatic condition, sex and gonadal developmental stages). A generalized linear model found somatic growth rates significantly different across regions. Whole otolith chemical signatures exhibited distinct regional patterns, mainly driven by differences in Ba/Ca, Cu/Ca, Li/Ca, Mg/Ca, Mn/Ca, Sr/Ca, and Zn/Ca. Combining somatic and reproductive data with multi-elemental signatures, the leave-one-out reclassification reassigned the individuals to their areas of origin with a high accuracy (100%, 93% and 87% for RJ, SC and RS, respectively). The results indicate a spatial isolation for the RJ individuals and some degree of intermixing between SC and RS. The data suggest that these fishing grounds should be considered as two stocks (RJ and SC+RS) for fisheries management purposes, although the southern stock is not necessarily homogeneous.